2015
DOI: 10.1371/journal.pone.0135720
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiles of Human Lung Epithelial Cells A549 Interacting with Aspergillus fumigatus by RNA-Seq

Abstract: Lung epithelial cells constitute the first defense line of host against the inhaled Aspergillus fumigatus; however, the transcriptional response of human alveolar type II epithelial cells was still unclear. Here we used RNA-Seq technology to assess the transcriptome profiles of A549 cells following direct interaction with conidia of A. fumigatus. The total number of identified genes was 19118. Compared with uninfected A549 cells, 459 genes were differentially expressed in cells co-incubated with conidia for 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
56
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 46 publications
3
56
3
Order By: Relevance
“…Furthermore, acting as an epithelial‐mesenchymal trophic unit, injured airway epithelial cells signal to underlying mesenchymal cells and vice versa . A fumigatus up‐regulates a number of key cytokines in airway epithelial cells . Intriguingly in the present study, we found that both A fumigatus spores and culture filtrate also caused an up‐regulation of ET‐1 in airway epithelial cells, with no significant change detected for TGF‐β1 or periostin and a decrease in TGF‐β2 compared with untreated controls.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Furthermore, acting as an epithelial‐mesenchymal trophic unit, injured airway epithelial cells signal to underlying mesenchymal cells and vice versa . A fumigatus up‐regulates a number of key cytokines in airway epithelial cells . Intriguingly in the present study, we found that both A fumigatus spores and culture filtrate also caused an up‐regulation of ET‐1 in airway epithelial cells, with no significant change detected for TGF‐β1 or periostin and a decrease in TGF‐β2 compared with untreated controls.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, signalling through an epithelial‐mesenchymal trophic unit (EMTU) may enable epithelial cells to regulate fibroblast behaviour in the subepithelial layer so governing the extent of repair following airway damage. Previous studies have shown that airway epithelial cells respond to germinating spores and hyphae of A fumigatus via production of a number of key cytokines including IL6, IL8, GM‐CSF and TNF‐α . In addition, we and others have established that inhalation of components of A fumigatus in vivo elicits airway inflammatory and remodelling responses through release of secreted fungal products including allergens with protease activity .…”
Section: Introductionmentioning
confidence: 92%
“…This has uncontrollable effects on the physiology of the cultured cells and therefore requires careful interpretation of the data and verification of the results in more physiological settings (see (14) and references therein). Furthermore, only very few studies were undertaken to obtain a comprehensive characterization of the molecular response of AEC II to the fungal insult (18).…”
mentioning
confidence: 99%
“…Analysis of changes in this intrinsic antiviral pathway in response to IBV infection is critical to elucidate IBV-host interaction. In this study, we examined IBV infection induced response in human lung epithelial A549 cells, a well characterized cell system that responds to infection robustly and has been extensively used to investigate innate immune response of pathogens, including but not limited to Ebola virus [40], Influenza A virus [41][42][43], Aspergillus fumigatus [44], Newcastle Disease Virus [45]. Our results generated a number of interesting observations.…”
Section: Discussionmentioning
confidence: 94%